Political activism in Iran: strategies for survival, possibilities for resistance and authoritarianism. Issue 6 (19th September 2017) - Rivetti, Paola
ABSTRACT: This article examines mobilizations and activism in authoritarian settings by considering the case of Iran. By focusing on the transformation of activism since the 1990s and the green movement, it advances an explanation of how oppositional political groups have been able to survive and produce forms of resistant subjectivity despite authoritarian constraints. In order to do so, the article brings together two scholarly traditions, namely Social Movement Theory (SMT) and the study of subjectivity and resistance as framed by Sari Hanafi. SMT explains how activists have been able to navigate repression and create opportunities for mobilization while shifting between formal and informal politics. The study of subjectivity helps conceptualize the type of subjects or political citizens that authoritarian environments generate. The article builds on field research with activists conducted in Iran and Turkey between 2007 and 2016. It argues that authoritarian constraints allow autonomous activism to flourish while emptying of meaning the regime-sanctioned political infrastructures.